SOCIAL SOLIDARITY OF STUDENTS IN STATE SMA KUPANG CITY: Student Solidarity Research in Kupang City High School - toineno, fespy oristo (Advances in Social Sciences Research Journal, 2019)
SOCIAL SOLIDARITY OF STUDENTS IN STATE SMA KUPANG CITY Fespy O. Toineno, S.Pd, Prof. Dr. Muhammad Akhyar, M.Pd, Prof. Dr. Nunuk Suryani, M.Pd Email: 1 fespyoristo@yahoo.com, 2 makhaliya@yahoo.com, 3 nunuk_suryani_uns@yahoo.com History Education Postgraduate Program, Sebelas Maret State University Surakarta ABSTRACT Social solidarity is the togetherness of individuals or groups that arise from moral feelings and shared beliefs that are reinforced by shared emotional experiences. Durkheim in Maliki said, there are two social solidarity namely mechanical solidarity and organic solidarity. Mechanical solidarity is an individual's awareness in carrying out social life based on the foundation of identity among its members. Whereas organic solidarity is an awareness developed on the basis of social cohesion through different solidarity models within the class of its members. This research uses descriptive qualitative method, research location in the city of Kupang. Data collection is done through library research, observation, in-depth interviews, and documentation techniques. The informants in this study were students of the State Senior High School in Kupang. Data analysis techniques used in this study were by means of data collection, data reduction, data presentation and drawing conclusions. The results showed that organic social solidarity was quite prominent in students. In the process of student social interaction, organic solidarity is more prominent. This is seen through one of the student activities in the learning process such as the division of study groups. The behavior of choosing friends according to liking, emotional closeness is very prominent. While the division of student roles is going well, but individuality or competition in groups and competition with other groups of students is inevitable. Keywords: Solidarity, Social, Students, Schools